Effect of Shikonin Against Candida albicans Biofilms - Yan, Yu; Tan, Fei; Miao, Hao; Wang, Hui; Cao, YingYing (Frontiers in Microbiology, 2019)
Candidiasis is often associated with the formation of biofilms. Candida albicans biofilms are inherently resistant to many clinical antifungal agents and have increasingly been found to be the sources of C. albicans infections. Novel antifungal agents against C. albicans biofilms are urgently needed. The aim of this study was to investigate the effect of shikonin (SK) against C. albicans biofilms and to clarify the underlying mechanisms. XTT reduction assay showed that SK could not only inhibit the formation of biofilms but also destroy the maintenance of mature biofilms. In a mouse vulvovaginal candidiasis (VVC) model, the fungal burden was remarkably reduced upon SK treatment. Further study showed that SK could inhibit hyphae formation and reduce cellular surface hydrophobicity. Real-time reverse transcription-PCR analysis revealed that several hypha- and adhesion-specific genes were differentially expressed in SK-treated biofilm, including the downregulation of ECE1, HWP1, EFG1, CPH1, RAS1, ALS1, ALS3, CSH1 and upregulation of TUP1, NRG1, BCR1. Moreover, SK induced the production of farnesol, a quorum sensing molecule, and exogenous addition of farnesol enhanced the antibiofilm activity of SK. Taken together, these results indicated that SK could be a favorable antifungal agent in the clinical management of C. albicans biofilms.